Social media, polarization and democracy: A multi-methods analysis of polarized users' interactions on Reddit's r/WallStreetBets - Elsa Massoc; Maximilian Lubda (Leibniz Institute for Financial Research SAFE, 2022)
In times of increased political polarization, the continuing existence of a deliberative arena where people with antagonistic views may engage with each other in non-violent ways is critical for democracy to live on. Social media are usually not conceived as such arenas. On the contrary, there has been widespread worry about their role in increasing polarization and political violence. This paper suggests a more positive impact of social media on democracy. Our analysis focuses on the subreddit "r/WallStreetBets" (r/WSB) - a finance-related forum that came under the spotlight when its users coordinated a financial attack on hedge funds during the Gamestop saga in early 2021. Based on an original method attributing partisanship scores to users, we present a network analysis of interactions between users at the opposite sides of the political spectrum on r/WSB. We then develop a content analysis of politically relevant threads in which polarized users participate. Our analyses show that r/WSB provides a rare space where users with antagonistic political leanings engage with each other, debate, and even cooperate.
Keywords: 330; social media; polarization; democracy; investment forum; social media; polarization; democracy; investment forum